Influence of Two Root Canal Obturation Techniques with Resin Based Sealer to Enterococcus faecalis Penetration - Aryadi Subrata; Anastasia Elsa Prahasti; Bernard Ongki Iskandar (Journal of Indonesian Dental Association, 2019)
Introduction: Root canal treatment is done to maintain the teeth to last as long as possible in the oral cavity. This can be done with three main stages, such as biomechanical preparation, sterilization and root canal filling. The hermetic seal of root canal filling has an important role in the success of root canal treatment. Objective: The aim of this in-vitro study is to compare the microbial leakage of root canals filled with RealSeal sealer/Resilon Points and AH Plus sealer/conventional gutta-percha points using single cone obturation technique and warm vertical compaction technique. Methods: Thirty-two extracted human mandibular premolars with single canals were decoronated to a standardized root length of 15 mm and prepared using crown-down technique to a master apical file size 30/.09. Teeth were divided into four experimental groups (n = 7 each group) and controls (n = 1 each group). Teeth in the first group were obturated using single master gutta percha cone and AH Plus sealer and second group were obturated with single Resilon gutta percha cone using RealSeal sealer. Third experimental group was filled with warm vertical condensed gutta-percha using AH Plus sealer and fourth group was filled with warm vertical condensed Resilon gutta-percha using RealSeal sealer. The coronal chamber of each sample were inoculated with Enterococcus faecalis. Results: There were no significant differences between the four experimental groups (P = 0.182). The differences occurred only in the survival time from each group. Group 4 (Warm Vertical Condensation - RealSeal) has the lowest leakage rate among other groups and the fastest leakage occurred in group 1 (Single Cone - AH Plus). Conclusion: The single-cone techniques does not insure durable apical seal against bacterial leakage. Warm vertical compaction technique using Resilon gutta-percha and RealSeal sealer appears to be more effective in minimizing bacterial leakage than gutta-percha and AH Plus sealer.